NILAI-NILAI PENDIDIKAN KARAKTER DALAM NOVEL NEGERI DI UJUNG TANDUK KARYA TERE LIYE - Suriawati, . (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract This research occurs as writers’ pretension to find what are the values of character education in the novel Negeri di Ujung Tanduk by Tere Liye. The problems that will discuss in this research are truth value, responsibility value, intelligent value, care value, and teamwork value and implementation of character education’s values in Bahasa Indonesia lesson grade Senior High School. The method used in this research is descriptive qualitative. The approachement is Sosiology Literature approach. The data source is novel Negeri di Ujung Tanduk by Tere Liye, moreover the data in this research is the quotation from the novel itself. The result of this research is about value of character education which including in the novel concerning (1) truth value; (2) the value of responsibility; (3) the value of dilligence; (4) the value of care; (5) the value of teamwork; and (6) the plan of implementation of character education value to bahasa Indonesia lesson which is view from curriculum aspect, including the lesson objection, the selection of teaching material, and grade of appropriate reading become lesson material for students grade XII of senior high school. Keywords: The Value of Character Education, Novel